The science and engineering of materials - Askeland, Donald R.; Wright, Wendelin J. (Cengage Learning, 2016)
The seventh edition of this text contains over 200 new homework problems and more than 50 new photos. It provides an understanding of the relationship between structure, processing, and properties of materials.